Struggle in the ethics of technology - Schuurman, E. (Koers, 2006)
The advantages as well as the disadvantages of modern technology, especially in combination with the development of the natural sciences, call in general for philosophical reflection. There is a struggle going on between the various philosophical movements. What is the content of Christian-philosophical thinking about technology and its problems? And what are the consequences in relation to the ethics of technology? Such questions are very unusual among Christians. Nevertheless, the potentially disastrous effects of technology require an ethics of technology. Such an ethics must concern itself with man’s good and responsible conduct in and through technology. Generally speaking, since modern times there has been a technological control mentality. All questions relating to spiritual reflection and religious problems are ruled out. The world view has been transformed to a technological worldview. Motives, values and norms are derived from it. This implies a technological ethics which is the cause of many threats and problems. It is characterised by a cosmological deficit and an ethical deficit. It is only possible to overcome these deficits by a reorientation in culture and in ethics. The “Enlightenment” ought to be enlightened itself by the God-given revelation. The cosmology of the reality as God’s creation and the commandments of love give a possibility for the redirection of an ethics of technology. A responsible cultural and technological development evokes a representation of culture that depicts earth as a garden tended by humans. Technology must be developed within the perspective of the earth as one large garden-city. Technology ought to serve life and not to threaten it. Besides, in an ethics of responsibility attention is given to the central motive of love against the central motive of power of the technological worldview. For a justified, responsible technology the ethical challenge is finding not only true motives, but also environment values, technological values and social values. Furthermore, technology has to obey a large number of normative principles and related norms. At the end of the article attention is paid to the consequences for praxis of this ethical-philosophical view and to the differences from those views which are currently held. The perspective of an ethics of technology ought not to be on doing things right, but on doing the right things.